2016
DOI: 10.5527/wjn.v5.i4.339
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive renal Rel/nuclear factor-κB expression in Lewis polycystic kidney disease rats

Abstract: Author contributions: Schwensen KG conducted the animal study, performed sample collection and histological staining; Ta MHT performed the immunofluorescence, Western blotting, and qPCR experiments, analyzed data and drafted the manuscript; Huso DL and Watnick T developed the Pkd2 knockout mouse model and provided paraffin embedded sections that were utilized for staining; Liuwantara D assisted with data interpretation and provided technical guidance with experimental methods; Rangan GK conceived of the study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 55 publications
(93 reference statements)
2
16
0
Order By: Relevance
“…We hypothesised that sirolimus would negatively regulate NF-κB via mTOR in PKD, but found that it did not alter the renal expression of the p65 DNA binding activity, p-p105, or NF-κB-dependent genes TNFα and CCL2 . A previous study in LPK rats demonstrated that renal TNFα and CCL2 are elevated in the late stages of disease (week 10 to 20) [ 22 ], and our current data shows that sirolimus was ineffective in suppressing transcription these genes. Further in vitro studies in cystic renal cells are required to prove a direct linkage between NF-κB and mTOR.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We hypothesised that sirolimus would negatively regulate NF-κB via mTOR in PKD, but found that it did not alter the renal expression of the p65 DNA binding activity, p-p105, or NF-κB-dependent genes TNFα and CCL2 . A previous study in LPK rats demonstrated that renal TNFα and CCL2 are elevated in the late stages of disease (week 10 to 20) [ 22 ], and our current data shows that sirolimus was ineffective in suppressing transcription these genes. Further in vitro studies in cystic renal cells are required to prove a direct linkage between NF-κB and mTOR.…”
Section: Discussionsupporting
confidence: 53%
“…Three studies were undertaken: (i) Study 1 : To determine the time-dependent changes in the expression of downstream targets for TORC1 (phosphorylated S6 ribosomal protein and 4E-BP1) and TORC2 (phosphorylated Akt) in male Lewis and LPK rats with disease progression, kidney tissue was examined at postnatal weeks 1, 3, 6, 10, 16 and 20 (n = 3 for Lewis and n = 6 for LPK per timepoint) using archival tissue from another experiment [ 22 ]; (ii) Study 2 : To determine the effects of early treatment with sirolimus on renal cystic disease in LPK rats, three week old male rats received either the vehicle or sirolimus (0.2 mg/kg per day by intraperitoneal injection for 5 days per week) from week 3 until week 10 (n = 9 for LPK+sirolimus, n = 11 for LPK+vehicle). Age-matched male Lewis animals received either sirolimus or vehicle (n = 4 per group).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot was done using a previously described method. 36 Blots were probed with NF-jB p105/p50 (1:1000, ab32360, Abcam) and b-actin (1:1000, #4970, Cell Signaling) and visualized on an Odyssey Imaging System (Licor). Densitometry was quantified using ImageJ (v1.47, National Institutes of Health, United States) and normalized using b-actin.…”
Section: Western Blotmentioning
confidence: 99%
“…NF-κB consists of a family of transcription factors that play critical roles in inflammation, as well as cell proliferation, differentiation, and survival [110]. Several in vitro studies, as well as experimental animal models and human studies have shown persistent activation of NF-κB and its pathogenic role in mediating chronic inflammation in CKD [111][112][113][114]. This redox-sensitive transcription factor can modulate DNA-binding activity of its multiple homo-and heterodimers, activate or inactivate the inhibitory κB kinase complex, or activate NF-κB by alternative inhibitor κBα phosphorylation [115].…”
Section: Ros In Inflammation and Fibrosismentioning
confidence: 99%